Controlling Mechanized Technological Processes of Grain Crop Cultivation - G. L. Utenkov; I. P. Dobrolyubov (Сельскохозяйственные машины и технологии)
The authors have proved that grain crops in Siberia are cultivated using primarily extensive technologies and inadequate technical support, which makes farm produce uncompetitive. Further intensification of crop cultivation requires increasing the accuracy of technological operations. However, the insufficient availability of modern machinery remains the main limiting factor in the technological modernization of agriculture. The study has revealed that further prospects for the efficiency growth in using mechanized technologies for cultivating grain crops are offered by soil cultivation, which consumes from 30 to 40 percent of all energy costs. (Research purpose) is to justify the methodological principles of automatic controlling an energy-intensive process of tillage in agricultural technologies of grain cultivation. (Materials and methods) Use has been made of the methods of statistical analysis and synthesis of technical control means. (Results and discussion) The study has proved the necessity of the intellectualization of farm production. The authors have developed a system of automatic mode regulation belonging to the class of automatic adaptive systems with programmable positional control of input data and ensures that the machine-and-tractor unit is in the optimal range of energy modes. The minimum of dynamic error has been accepted as the quality criterion of the positional control system. To measure it, use has been made of Mahalanobis-type metric taking account of the Hamming distance. The operation of a machine-and-tractor unit has been controlled by power and kinematic regulation of the engine operating modes on tractors with a hydraulic gearbox and a gas-turbocharged engine. The effect was directed on the fuel pump rail or the fuel control lever, the gear shift lever, and the hydraulic system levers. (Conclusions) The study has revealed a random nature of the change in traction resistance of the machine-and-tractor unit caused by the heterogeneity of the soil cover. The authors have determined that this leads to increased energy intensity, as well as insufficient performance of built-in information systems indicating the current energy modes of operation of the machine-and-tractor unit operation. To control and regulate the soil heterogeneity by its hardness, a new technical solution has been proposed. The authors have proved that the developed and tested theoretical foundations and technical means of automatic control of energy-intensive technological processes of tillage ensure the required quality indicators.